Is Social Work Evidence-based? Does Saying So Make It So? Ongoing Challenges in Integrating Research, Practice and Policy. (13th July 2016) - Gambrill, Eileen
ABSTRACT: The integration of research and practice is of concern in all helping professions. Has social work become an evidence-based profession as some claim? Characteristics of current-day social work are presented that dispute this view, related continuing concerns are suggested, and promising developments (mostly outside social work) are described that should contribute to the provision of evidence-informed services to clients.